Technology forecasting by analogy and technology assessment on the drug profiling system for implementation at the Philippine Drug Enforcement Agency (PDEA) - Domingo, Maria Therese Anne L. (Quezon City, Philippines Technology Management Center, 2014)
The illicit manufacture, trafficking, and use of illicit drugs particularly methamphetamine hydrochloride constitute one of the most significant drug problems worldwide. Illicit drugs continue to pose a threat to a country's security and stability while at the same time jeopardizing the health and welfare of its citizens. The high demand for drugs and the massive profits generated by their trade continue to provide ample incentive for manufacturers and traffickers to expand their illicit business. This increase in the local availability and consumption of illicit drugs highlighted the need for a more innovative and focused approach that will counter this global drug problem. In the Philippines, the demand for drugs has not been substantially reduced. The Philippine Drug Enforcement Agency (PDEA) is the lead anti-drugs law enforcement agency in the country responsible for preventing, investigating, and combating dangerous drugs, controlled precursors and essential chemicals. With its vision to provide a drug-free Philippines by 2020, PDEA needs to implement innovative measures that will help them suppress the supply of dangerous drugs. The gaps in the availability and analysis of data in relation to all aspects of the drug phenomenon limit their understanding of the drug market dynamics which consequently hindrances them in developing appropriate action and intervention that will suppress the growing problem of illicit drugs. The technology of interest for this study is drug profiling. The rationale for the implementation of a forensic drug profiling system is to serve as an additional tool to identify targets or groups involved in organized crime by linking seized drugs with individuals involved in drug production and/or trafficking. The competitive advantages and benefits of drug profiling as an intelligence-gathering process for law enforcers are analyzed using a combination of technology forecasting by analogy and technology assessment tools. Analyses showed the country's potential acceptance of the technology as well as its capability to implement it.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Philippine Drug Enforcement Agency (PDEA); Technology assessment